Functional prediction of miR-3144-5p in human cardiac myocytes based on transcriptome sequencing and bioinformatics. Issue 32 (August 2017) - Ruan, Lei; Yang, Yi; Huang, Yi; Ding, Ling; Zhang, Cuntai; Wu, Xiaofen
Abstract: Background: RAN guanine nucleotide release factor ( RANGRF ) encoding protein MOG1 plays an important role in cardiac arrhythmia, so we intended to investigate the regulatory miRNA of RANGRF and explore its potential regulatory mechanism in arrhythmogenesis. Methods: Based on bioinformatic analysis, miR-3144-5p was predicted to be a regulatory miRNA of RANGRF, which were then validated through a dual-luciferase reporter plasmid assay. Subsequently, the expression level of miR-3144-5p in human cardiac myocytes (HCMs) was detected, followed by cell transfection with miR-3144-5p mimics. Transcriptome sequencing was then performed in HCMs with or without transfection. The sequencing results were subjected to bioinformatic analyses, including differentially expressed gene (DEG) analysis, functional enrichment analysis, protein–protein interaction (PPI) network analysis, miRNA-target gene analysis, and miRNA-transcription factor (TF)-target gene coregulatory network analysis. Results: There really existed a regulatory relation between miR-3144-5p and RANGRF . The expression level of miR-3144-5p was low in HCMs. After cell transfection, miR-3144-5p expression level significantly increased in HCMs. Bioinformatic analyses of the transcriptome sequencing results identified 300 upregulated and 271 downregulated DEGs between miR-3144-5p mimic and control group. The upregulated genes ISL1 and neuregulin 1 ( NRG1 ) were significantly enriched in cardiac muscle cell myoblast differentiation (GO:0060379). CCL21 was one of the hub genes in the PPI network and also a target gene of miR-3144-5p. Moreover, the TF of v-Myc avian myelocytomatosis viral oncogene neuroblastoma-derived homolog (MYCN) was involved in the miR-3144-5p-TF-target gene coregulatory network and interacted with the target genes of miR-3144-5p. Conclusion: ISL1, NRG1, CCL21, and MYCN were differentially expressed in the miR-3144-5p mimic group, suggesting that miR-3144-5p overexpression plays a role in HCMs by regulating these genes and TF. This study may provide new insight into the mechanisms behind the progression of cardiac arrhythmia.